The demographic development and its impact on macroeconomic development : the case of Moldova and Romania - Gutanu, Maria; Šíma, Ondřej; Dudzich, Viktar; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
This thesis offers a generous description of the global demographic development of the recent past, with special attention granted to international migration and population ageing, and its impact on the macroeconomic development of the countries. This is practically illustrated using the example of Moldova and Romania – two countries, which face the process of ageing of their population at a relatively faster rate than other countries in the history of humankind.
Vedoucí práce: Ondřej Šíma
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses